The Eco RI-induced band pattern in buffalo chromosomes - TOMAR, S S; GOSWAMI, S L (The Indian Journal of Animal Sciences, 2014)
The longitudinal differentiation of fixed metaphase chromosomes of Murrah and Nili Ravi breeds of buffalo was studied by digestion with restriction endonuclease (RE) Eeo Ri and subsequently staining with Giemsa. All the chromosomes of both the breeds exhibited G-like band pattern. Breed differences could not be detected for banding pattern. The standardized band pattern on first 5 autosomes and X-chromosome of buffaloes was prepared. The results suggested that the structural organization of specific chromosomo region playa primary role in determining the cytological effect after RE treatment.